2021
DOI: 10.3390/ijerph182010584
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Life Satisfaction in Colombian Older Adults

Abstract: Background. Effective coping strategies facilitate older adults’ optimal adaptation and contribute to their well-being. Problem-focused strategies are associated with active styles and enhance well-being. This study analyzes the role of coping strategies in Colombian older adults’ subjective well-being (SWB) using structural equation modelling. Additionally, Confirmatory Factor Analyses of the Life Satisfaction Scale and Coping Strategies Questionnaires are performed. Method. A cross-sectional study is conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Moreover, coping style significantly affects anxiety, depression, 32 and life satisfaction 69 . Problem‐focused strategies, which represent an active coping style, have been linked to improved well‐being 17 . However, these studies did not investigate the role of anxiety and depression in mediating the relationship between coping styles and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, coping style significantly affects anxiety, depression, 32 and life satisfaction 69 . Problem‐focused strategies, which represent an active coping style, have been linked to improved well‐being 17 . However, these studies did not investigate the role of anxiety and depression in mediating the relationship between coping styles and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is now understood that individuals with active coping styles are more prone to take constructive actions, including thinking positively and finding appropriate solutions. Individuals using active coping strategies deal with negative emotions by adopting positive cognition and seeking help, which benefits individuals in solving problems and ameliorating negative emotions such as anxiety and depression and is associated with higher well‐being 17 . In contrast, passive coping strategies include refusing to acknowledge the existence of stressful events, running away from the present problem, and giving up trying to pursue goals, which strengthens the feeling of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Coping with changes in ageing, understanding these changes and introducing appropriate coping strategies make seniors accept changing social roles and economic, health, physical and intellectual conditions. With this approach, they use AA opportunities appropriately [4,6,19,27,28,39,41,46,51]. Determining strategies to cope with various situations by seniors, their regular physical activity improves health and enables an independent lifestyle, which consequently means a higher level of well-being [49,51,52].…”
Section: Challenges and Opportunities Of Aamentioning
confidence: 99%
“…Mediating role of anxiety and depression in the relationship between coping styles and life satisfaction Previous studies showed that coping style signi cantly affects anxiety, depression [32] and life satisfaction [69]. Problem-focused strategies are active coping styles associated with enhanced wellbeing [17]. However, they did not examine the mediating effect of anxiety or depression on the relationship between coping styles and life satisfaction.…”
Section: Correlations Among Anxiety Depression Life Satisfaction and ...mentioning
confidence: 99%
“…Passive coping strategies include refusing to acknowledge the existence of stressful events, running away from the present crisis, giving up trying to pursue goals and strengthening the feeling of pressure. Active coping was associated with higher wellbeing [17], while passive coping was often related to psychological distress, anxiety, and depression [18]. Individuals with active coping styles are more prone to take constructive actions, including thinking positively and nding appropriate solutions.…”
Section: Introductionmentioning
confidence: 99%